NFAT5 and HIF-1α Coordinate to Regulate NKCC1 Expression in Hippocampal Neurons After Hypoxia-Ischemia - Yang, Xing-Liang; Zeng, Meng-Liu; Shao, Lin; Jiang, Guang-Tong; Cheng, Jing-Jing; Chen, Tao-Xiang; Han, Song; Yin, Jun; Liu, Wan-Hong; He, Xiao-Hua; Peng, Bi-Wen (Frontiers in Cell and Developmental Biology, 2019)
Hypoxic-ischemic encephalopathy (HIE) is a serious birth complication with severe long-term sequelae such as cerebral palsy, epilepsy and cognitive disabilities. Na+-K+-2Cl− cotransporters 1 (NKCC1) is dramaticly upregulated after hypoxic-ischemia (HI) which aggravates brain edema and brain damage. Clinically, NKCC1 specific inhibitor-bumetanide was used to treat diseases related to NKCC1 aberrant expression, but the underlying mechanism of NKCC1 expression is hardly studied in HIE. In this study, the cooperation between hypoxia-inducible factor-1α (HIF-1α) and NFAT5 in NKCC1 expression was found in hippocampal neurons under hypoxic condition. HI increased HIF-1α nuclear localization and transcriptional activity, and pharmacological inhibition of the HIF-1α transcription activity or mutation of hypoxia responsive element (HRE) motifs recovered hypoxia-induced aberrant expression and promoter activity of NKCC1. In contrast, reverse OGD-induced downregulation of nuclear factor of activated T cells 5 (NFAT5) expression by hypertonic saline treatment hijacked NKCC1 upregulation. More importantly, knocking down NFAT5 or mutation of tonicity enhancer element (TonE) stimulated NKCC1 expression and promoter activity under normal physiological condition. The positive regulation of NKCC1 by HIF-1α and negative regulation of NKCC1 by NFAT5 may serve to maintain NKCC1 expression levels, which may shed light on the transcription regulation of NKCC1 in hippocampal neurons after hypoxia insult.